Use of First Language in English Language Teaching: EFL Teachers’ Perspectives - Hari Prasad Tiwari (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2024)
First language (L1) is seen as a tool that aids in teaching the second language (L2). However, an over-reliance on L1 can slow down the learning process and prevent the achievement of true L2 fluency. This qualitative study aims to investigate the role of the L1 in L2 instruction, particularly its potential to both aid and hinder the learning process. The study employs an interpretive approach, focusing on the perspectives of 14 college-level English as a Foreign Language (EFL) teachers. These participants were selected using judgmental sampling. Data was collected through semi-structured interviews and subsequently analyzed using a thematic approach. The findings indicate that teachers utilize L1 in various ways, including enhancing comprehension, assisting lower-level students, saving time, recapturing students’ attention, and introducing new vocabulary. The study concludes that while L1 can serve as a valuable tool in L2 instruction, its use should be strategic to optimize learning outcomes. It highlights how L1 can act as a bridge to aid L2 learning, indicating the need for a balanced usage.